Aptes-phosphoric acid composite coated modified low-loss fe-si magnetic powder core and a preparation method thereof

CN122991840APending Publication Date: 2026-10-27GUANGDONG INST OF NEW MATERIALS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611155594.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]目前,铁硅软磁复合材料中存在着如下问题:(1)绝缘性与热稳定性的不可调矛盾:有机包覆层(如树脂)虽柔韧性好但耐温不足(<300℃),无法匹配铁硅磁粉芯必需的去应力退火温度,高温下分解碳化导致绝缘崩溃;无机磷酸盐层虽耐热但本身脆性大(P-O网络刚性过强),在高压压制时易产生微裂纹,导致绝缘电阻提升有限;(2)界面结合机制薄弱(物理附着为主):传统单一磷酸盐包覆仅依靠金属表面微粗糙结构的机械锚固和少量离子键,在后续大压应力成型及冷热循环服役中,界面易脱粘剥离,形成局部导电通路

Benefits of technology

(1)协同保护机制:内层磷酸盐耐热,外层APTES柔韧抗裂,弥补单一包覆层的不足,兼顾高温稳定性和力学完整性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122991840A_ABST
    Figure CN122991840A_ABST
Patent Text Reader

Abstract

The application discloses an APTES-phosphoric acid composite coated modified low-loss iron-silicon magnetic powder core and a preparation method thereof, and belongs to the technical field of chemical materials.The preparation method of the iron-silicon magnetic powder core comprises the following steps: activating iron-silicon powder with an acid solution; mixing the activated iron-silicon powder with a phosphoric acid solution, stirring and reacting to obtain a reaction system 1; mixing the reaction system 1 with iron phosphate and / or silicon phosphate, uniformly stirring to obtain a reaction system 2; mixing gamma-aminopropyl triethoxysilane with an alcohol-water mixed solvent, hydrolyzing to obtain an APTES pre-hydrolysis solution; mixing the APTES pre-hydrolysis solution with the reaction system 2, stirring and reacting to obtain a reaction system 3; filtering and washing the reaction system 3, collecting a product, shaping and annealing to obtain the iron-silicon magnetic powder core.The application improves the insulation resistance and magnetic permeability of the iron-silicon magnetic powder core, reduces the total loss, and the interface bonding state is dense and uniformly anchored, and the moisture and heat resistance retention rate is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of soft magnetic materials technology, and in particular to a low-loss iron-silicon magnetic powder core modified with APTES-phosphate composite coating and its preparation method. Background Technology

[0002] Ferro-silicon (Fe-Si) alloy powder is widely used in the manufacture of molded inductors, power inductors, and high-frequency magnetic components due to its high saturation magnetic flux density, good DC bias characteristics, and low magnetostriction coefficient. However, with the development of electronic devices towards higher frequencies and smaller sizes, higher requirements are placed on the loss characteristics of the magnetic powder core. Ferro-silicon powder is prone to large eddy current losses under high-frequency operating conditions, and its surface chemical properties are active, making it susceptible to oxidation and corrosion in humid and hot environments, leading to deterioration of magnetic properties. Therefore, insulating the ferro-silicon powder is crucial for reducing losses and improving reliability.

[0003] At present, there are the following problems in iron-silicon soft magnetic composite materials: (1) The irreconcilable contradiction between insulation and thermal stability: Although organic coating layers (such as resin) are flexible, they are not resistant to temperature (<300℃), which cannot match the stress relief annealing temperature required for iron-silicon magnetic powder cores. Decomposition and carbonization at high temperature leads to insulation collapse; Although inorganic phosphate layers are heat resistant, they are brittle (PO network is too rigid), and microcracks are easily generated when pressed under high pressure, resulting in limited improvement in insulation resistance; (2) Weak interface bonding mechanism (mainly physical adhesion): Traditional single phosphate coating relies only on the mechanical anchoring of the micro-rough structure of the metal surface and a small number of ionic bonds. In subsequent high compressive stress molding and cold and hot cycle service, the interface is easy to debond and peel off, forming a local conductive path.

[0004] Chinese patent CN103862033A discloses a method for coating iron powder surface. The prepared coated powder has a double-layer coating structure of phosphate and siloxane layers. However, it does not contain silicon and its electromagnetic properties still need to be improved. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide an APTES-phosphate composite coated and modified low-loss iron-silicon magnetic powder core and its preparation method.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a method for preparing an iron-silicon magnetic powder core, comprising the following steps: S1: Activate iron-silicon powder with acid solution to obtain activated iron-silicon powder; S2: Mix the activated iron-silicon powder from step S2 with phosphoric acid solution, stir and react to obtain reaction system 1; S3: Mix reaction system 1 with ferric phosphate and / or silicon phosphate, stir until homogeneous, and obtain reaction system 2; S4: Mix γ-aminopropyltriethoxysilane with an alcohol-water mixed solvent to obtain an APTES-alcohol-water mixed system, hydrolyze it to obtain an APTES pre-hydrolyzed solution; mix the APTES pre-hydrolyzed solution with the reaction system 2 described in step S3, stir and react to obtain reaction system 3; S5: The reaction system 3 is filtered and washed and the product is collected. After molding and annealing, the iron-silicon magnetic powder core is obtained.

[0007] The iron-silicon magnetic powder core of this invention consists of a composite coating layer structure composed of a dense phosphate bottom layer and an APTES cross-linked silane network outer layer. Through the chemical reaction of phosphate with iron and silicon elements on the surface of the iron-silicon powder, an in-situ phosphate conversion film of iron phosphate (FePO4) and silicon phosphate (Si3(PO4)4) is generated, forming an inorganic bottom layer chemically bonded to the iron-silicon matrix. This invention further incorporates free nano-iron phosphate and nano-silicon phosphate, which can physically embed into the micropores, cracks, or leaks of the phosphate conversion film, significantly improving the density of the insulating layer. The silanol groups (Si-OH) generated by the hydrolysis of γ-aminopropyltriethoxysilane dehydrate and condense with the active hydroxyl groups (P-OH) on the phosphate surface to form Si-OP covalent bonds, which graft and cross-link with the inorganic layer surface and free phosphate to form a dense organosilicon network outer layer. By constructing a double-layer structure covalently bonded to the iron-silicon matrix, the problems of brittleness, detachment, interface peeling and failure of the insulation layer during high-temperature molding and service are fundamentally solved, further improving the electromagnetic performance of the iron-silicon magnetic powder core.

[0008] Further, in step S1, the mass fraction of silicon in the iron-silicon powder is preferably 3% to 9%, for example, including but not limited to any point value or any range of two points from 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, and 9%.

[0009] Further, in step S1, the acid solution includes hydrochloric acid solution and / or sulfuric acid solution, and the volume concentration of the acid solution is preferably 1% to 5%, for example, including but not limited to any point value or any range of two points such as 1%, 2%, 3%, 4% and 5%.

[0010] Furthermore, in step S1, the activation time is preferably 1 to 5 minutes, for example, including but not limited to any point value or any range of two points such as 1 minute, 2 minutes, 3 minutes, 4 minutes and 5 minutes.

[0011] Furthermore, in step S2, the mass fraction of the phosphoric acid solution is preferably 1.5% to 4%, for example, including but not limited to any point value or any range of two points such as 1.5%, 2%, 2.5%, 3%, 3.5% and 4%.

[0012] Furthermore, in step S2, the stirring reaction temperature is preferably 40~80℃, for example, including but not limited to any point value or any range of two points among 40℃, 50℃, 60℃, 70℃ and 80℃. The stirring reaction time should be 10 to 60 minutes, including but not limited to any point value or any range of two points such as 10 min, 20 min, 30 min, 40 min, 50 min and 60 min. The pH value for the stirring reaction should ideally be between 3 and 5, including but not limited to any value from 3, 3.5, 4, 4.5, and 5, or any range consisting of two such values. Ensure that the inner layer does not experience over-corrosion and that the outer layer grafting density achieves saturated coverage.

[0013] Further, in step S3, the mass ratio of the iron-silicon powder to the iron phosphate is preferably 100:(0.5~1), for example, including but not limited to any point value or any range of two points among 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9 and 100:1; And / or, the mass ratio of the iron-silicon powder to silicon phosphate is preferably 100:(0.5~1), for example, including but not limited to any point value or any range of two points from 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9, and 100:1. Exceeding this range will cause particle agglomeration and magnetic dilution effects, leading to a significant decrease in magnetic permeability and an increase in losses.

[0014] Furthermore, in step S3, the mixing time is preferably 20 to 60 minutes, including but not limited to any point value or any range of two points such as 20 minutes, 30 minutes, 40 minutes, 50 minutes and 60 minutes.

[0015] Further, in step S3, after stirring evenly, the mixture is kept at a temperature of 40~80℃, including but not limited to any point value or any range of two points among 40℃, 50℃, 60℃, 70℃ and 80℃; the holding time is preferably 5~15 min, including but not limited to any point value or any range of two points among 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min and 15 min.

[0016] Further, in step S4, the mass ratio of the iron-silicon powder to γ-aminopropyltriethoxysilane is preferably 100:(0.5~5), for example, including but not limited to any point value or any range of two points from 100:0.5, 100:1, 100:1.5, 100:2, 100:2.5, 100:3, 100:3.5, 100:4, 100:4.5, and 100:5.

[0017] Furthermore, in step S4, the stirring reaction temperature is preferably 50~80℃, for example, including but not limited to any point value or any range of two points among 50℃, 60℃, 70℃ and 80℃. The stirring reaction time should be 30 to 120 minutes, including but not limited to any point value or any range of two points from 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min and 120 min.

[0018] Further, in step S4, the volume fraction of the alcohol-water mixed solvent in the APTES-alcohol-water mixed system is preferably 10% to 30%, for example, including but not limited to any point value or any range of two points such as 10%, 15%, 20%, 25% and 30%. The alcohol-water mixed solvent contains ethanol and water, and the volume ratio of ethanol to water is preferably ethanol:water = (1~4):1, for example, including but not limited to any point value or any range value composed of any two points such as 1:1, 1:2, 1:3 and 1:4.

[0019] Furthermore, in step S4, the hydrolysis temperature is preferably 30~70℃, for example, including but not limited to any point value or any range of two points among 30℃, 40℃, 50℃, 60℃ and 70℃; the hydrolysis time is preferably 10~30 min, for example, including but not limited to any point value or any range of two points among 10 min, 15 min, 20 min, 25 min and 30 min.

[0020] Furthermore, in step S5, the molding pressure is preferably 800~2500 MPa, for example, including but not limited to any point value or any range of any two points from 800 MPa, 900 MPa, 1000 MPa, 1100 MPa, 1200 MPa, 1300 MPa, 1400 MPa, 1500 MPa, 1600 MPa, 1700 MPa, 1800 MPa, 1900 MPa, 2000 MPa, 2100 MPa, 2200 MPa, 2300 MPa, 2400 MPa and 2500 MPa.

[0021] Further, in step S5, the product is mixed with a release agent and then cold-pressed; the release agent includes zinc stearate and / or magnesium stearate; the mass ratio of the product to the release agent is preferably product:release agent = 100:(0.5~2), for example, including but not limited to any point value or any range of any two points among 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9, 100:1, 100:1.1, 100:1.2, 100:1.3, 100:1.4, 100:1.5, 100:1.6, 100:1.7, 100:1.8, 100:1.9 and 100:2.

[0022] Furthermore, in step S5, the annealing temperature is preferably 500~900℃, for example, including but not limited to any point value or any range of two points among 500℃, 550℃, 600℃, 650℃, 700℃, 750℃, 800℃, 850℃ and 900℃; the annealing time is preferably 0.5~3 h, for example, including but not limited to any point value or any range of two points among 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h and 3 h.

[0023] Secondly, the present invention provides an iron-silicon magnetic powder core, which is prepared by the aforementioned preparation method.

[0024] Thirdly, the present invention provides the application of the iron-silicon magnetic powder core in the preparation of electromagnetic materials.

[0025] Furthermore, the electromagnetic material includes at least one of an inductor, a transformer, and a DC-DC converter.

[0026] Furthermore, the inductor includes at least one of a boost inductor, a filter inductor, and a resonant inductor.

[0027] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) Synergistic protection mechanism: the inner phosphate layer is heat resistant, and the outer APTES layer is flexible and crack resistant, which makes up for the shortcomings of a single coating layer and takes into account both high temperature stability and mechanical integrity. (2) Strong insulation and bonding: The silanol groups (Si-OH) of APTES can form strong chemical bonds (Si-OP covalent bonds) with the surface of the phosphate layer. At the same time, the silane network itself is tightly cross-linked, and the coating layer is not easy to peel off during high pressure molding, thus significantly improving the insulation performance. (3) Excellent corrosion resistance: The amino (-NH2) and long-chain alkyl groups at the end of APTES give the outer APTES silane film excellent hydrophobicity and chemical stability, which can effectively block the intrusion of water vapor and corrosive media, and significantly improve the corrosion resistance of iron-silicon powder in humid and hot environments. (4) Physical filling and insulation reinforcement: In-situ generated phosphate conversion films inevitably have micropores, cracks or leaks. The additional nanoscale (50~80nm) iron phosphate and / or silicon phosphate can be physically embedded in these defects, greatly improving the density of the insulation layer.

[0028] (5) Chemical dual anchoring effect: The silanol groups (Si-OH) generated by the hydrolysis of APTES mainly condense with the P-OH on the phosphate surface. The additional nano-phosphate provides a large number of additional P-OH active sites, making the APTES organic network grafted more densely and anchored more firmly.

[0029] (6) Composition compensation: Low silica powder: High surface iron activity, prone to over-corrosion, and insufficient in-situ generated silicon phosphate. Additional free silicon phosphate can compensate for the lack of silicon-rich insulating components and balance interfacial bonding. High silica powder: Difficult to form a film on the surface. Additional free iron phosphate can compensate for the lack of iron sites and ensure complete coverage of the inner phosphate layer; (7) Precise control of dosage: Excessive free phosphate will cause self-agglomeration, occupy the volume fraction of the magnetic phase, produce magnetic dilution and introduce internal stress. Therefore, the present invention determines the optimal dosage of free phosphate to prevent dilution effect and agglomeration.

[0030] (8) The present invention further improves the insulation resistance and permeability of the iron-silicon magnetic powder core, reduces the total loss, and has a dense and uniformly anchored interface bonding state with high moisture and heat retention rate. Attached Figure Description

[0031] Figure 1 This is a schematic SEM image of the iron-silicon magnetic powder core prepared in Example 4. In the image, a is a schematic SEM image of the iron-silicon magnetic powder core; b is a partial SEM image of the iron-silicon magnetic powder core.

[0032] Figure 2 This is a schematic SEM image of the iron-silicon magnetic powder core prepared in Example 1. In the image, a is a schematic SEM image of the iron-silicon magnetic powder core; b is a partial SEM image of the iron-silicon magnetic powder core.

[0033] Figure 3 This is a schematic SEM image of the iron-silicon magnetic powder core prepared in Example 6. In the image, a is a schematic SEM image of the iron-silicon magnetic powder core; b is a partial SEM image of the iron-silicon magnetic powder core. Detailed Implementation

[0034] To better illustrate the purpose, technical solution, and advantages of this invention, the invention will be further described below with reference to specific embodiments. Unless otherwise specified, other materials and reagents used in the embodiments are commercially available.

[0035] Example 1 Ferrosilicon powder: Fe-6.5Si gas-atomized ferrosilicon powder (silicon mass fraction 6.5%, oxygen mass fraction 0.005%, carbon mass fraction 0.005%, sulfur mass fraction 0.005%, phosphorus mass fraction 0.01%, iron mass fraction 93.475%), median particle size D 50 =25 μm.

[0036] 1. Acid pickling and activation Iron-silicon powder was immersed in 2% (v / v) dilute hydrochloric acid for 3 minutes to perform surface activation treatment, remove the surface oxide layer, and introduce active hydroxyl groups. It was then washed with deionized water until the pH was neutral, and vacuum dried to obtain activated iron-silicon powder.

[0037] 2. Phosphoric acid pre-coating The activated iron-silicon powder was added to a 2.5% phosphoric acid solution, the pH was adjusted to 4, and the mixture was stirred at 60°C for 30 min to obtain reaction system 1.

[0038] 3. Introduce free phosphate Add 0.5% of FePO4 powder (the mass ratio of FePO4 powder to FePO4 powder is 100:0.5, and the particle size of FePO4 powder is 50~80 nm) and 0.5% of Si3(PO4)4 powder (the mass ratio of FePO4 powder to Si3(PO4)4 powder is 100:0.5, and the particle size of Si3(PO4)4 powder is 50~80 nm) to reaction system 1. Stir at room temperature for 30 min to mix evenly, and keep at 60℃ for 10 min to obtain reaction system 2.

[0039] 4. APTES composite coating APTES (γ-aminopropyltriethoxysilane) was mixed with an alcohol-water mixed solvent to obtain an APTES-alcohol-water mixed system. This system was hydrolyzed at 50°C for 20 min to obtain a pre-hydrolyzed APTES solution. The pre-hydrolyzed APTES solution was added dropwise to reaction system 2, and the mixture was stirred at 60°C for 60 min to obtain reaction system 3.

[0040] In the APTES-alcohol-water mixed system, the volume fraction of the alcohol-water mixed solvent is 15%, the volume ratio of ethanol to water in the alcohol-water mixed solvent is 3:1, and the mass ratio of iron-silicon powder to APTES is 100:2.

[0041] 5. Separation and drying The reaction system 3 was filtered and washed with anhydrous ethanol, the powder was collected, and vacuum dried at 100℃ for 2 h to obtain APTES-phosphate composite coated modified iron-silicon powder.

[0042] 6. Core forming APTES-phosphate composite-coated modified iron-silicon powder was mixed with a release agent (the mass ratio of APTES-phosphate composite-coated modified iron-silicon powder to zinc stearate was 100:0.8), and cold-pressed under 1800 MPa pressure. The mixture was then annealed at 650℃ for 1 h in a nitrogen atmosphere to obtain an iron-silicon magnetic powder core.

[0043] Example 2 In the step of introducing free phosphate, only 1% of FePO4 powder (the mass ratio of iron-silicon powder to FePO4 powder is 100:1) is added to reaction system 1, without Si3(PO4)4 powder, and the other preparation methods are the same as in Example 1.

[0044] Example 3 In the step of introducing free phosphate, only 1% of the mass of iron-silicon powder, Si3(PO4)4 powder (the mass ratio of iron-silicon powder to Si3(PO4)4 powder is added to reaction system 1, without FePO4 powder. Other preparation methods are the same as in Example 1.

[0045] Example 4 The specifications of the iron-silicon powder used are: Fe-3Si gas-atomized iron-silicon powder (silicon mass fraction 3%, oxygen mass fraction 0.005%, carbon mass fraction 0.005%, sulfur mass fraction 0.005%, phosphorus mass fraction 0.01%, iron mass fraction 96.975%), median particle size D 50 =25 μm.

[0046] In step 2, the mass fraction of the phosphoric acid solution is 1.5% (due to the high iron activity on the low-silicon surface, the phosphoric acid concentration is reduced to prevent over-corrosion). Other preparation methods are the same as in Example 1.

[0047] Example 5 The specifications of the iron-silicon powder used are: Fe-9Si gas-atomized iron-silicon powder (silicon mass fraction 9%, oxygen mass fraction 0.005%, carbon mass fraction 0.005%, sulfur mass fraction 0.005%, phosphorus mass fraction 0.01%, iron mass fraction 90.975%), D 50 =25 μm.

[0048] The mass fraction of the phosphoric acid solution in step 2 is 4% (the phosphoric acid concentration is appropriately increased because it is difficult to form a film on a high-silica surface).

[0049] Example 6 In Example 1, FePO4 powder accounts for 1% of the mass of iron-silicon powder, and Si3(PO4)4 powder accounts for 1% of the mass of iron-silicon powder. Other preparation methods are the same as in Example 1.

[0050] Comparative Example 1 No free phosphate is introduced; the other preparation methods are the same as in Example 1.

[0051] Comparative Example 2 Without APTES composite coating, the other preparation methods are the same as in Example 1.

[0052] Comparative Example 3 No pre-coating with phosphate was performed; the other preparation methods were the same as in Example 1.

[0053] Comparative Example 4 No phosphate pre-coating was performed, no free phosphate was introduced, and the other preparation methods were the same as in Example 1.

[0054] Comparative Example 5 The specifications of the iron-silicon powder used are: Fe-1Si gas-atomized iron-silicon powder (silicon mass fraction 1%, oxygen mass fraction 0.005%, carbon mass fraction 0.005%, sulfur mass fraction 0.005%, phosphorus mass fraction 0.01%, iron mass fraction 98.975%), D 50 =25 μm.

[0055] The mass fraction of the phosphoric acid solution in step 2 is 0.8%, and the other preparation methods are the same as in Example 1.

[0056] Comparative Example 6 The specifications of the iron-silicon powder used are: Fe-4.5Si gas-atomized iron-silicon powder (silicon mass fraction 4.5%, oxygen mass fraction 0.005%, carbon mass fraction 0.005%, sulfur mass fraction 0.005%, phosphorus mass fraction 0.01%, iron mass fraction 95.475%), D 50 =25 μm.

[0057] The mass fraction of the phosphoric acid solution in step 2 is 2%, and the other preparation methods are the same as in Example 1.

[0058] Example of effect 1. Testing Method The iron-silicon magnetic powder cores prepared in the examples and comparative examples were tested. The cores were pressed into rings at 2000 MPa, with dimensions of 26.92 × 14.7 × 11.18 mm. After stress-relief annealing at 700℃, they were wound with enameled copper wire in 30 turns. The total loss was measured using a BH analyzer according to GB / T 3658-2022, and the permeability was measured using an impedance analyzer according to GB / T 28869.2-2023. The insulation resistance was measured using a TH2683 resistance tester with a test voltage set to 50V. The damp heat retention rate was tested after 500 h in a damp heat aging chamber at 85% humidity and 85℃. The iron-silicon magnetic powder cores prepared in the examples and comparative examples were observed using scanning electron microscopy (SEM).

[0059] 2. Test Results like Figure 1 a and Figure 1 Figure b shows a SEM image of the iron-silicon magnetic powder core prepared in Example 4. Figure 2 a and Figure 2 Figure b shows a SEM image of the iron-silicon magnetic powder core prepared in Example 1. Figure 3 a and Figure 3 Figure b shows a SEM image of the iron-silicon magnetic powder core prepared in Example 6. As shown in Table 1, the insulation resistance of Example 1 is as high as 6.80 × 10⁻⁶. 7 Ω·cm, while Comparative Example 1 is only 2.50×10 Ω·cm. 7 In Example 1, the insulation resistance was nearly doubled (Ω·cm), while the total loss decreased from 377 kW / m³ to 328 kW / m³. In Comparative Example 2, the insulation resistance plummeted to 0.085 × 10⁻⁶ Ω·cm. 7The Ω·cm (nearly conductive) indicates that free salt, without being anchored by APTES, cannot form an effective insulating network and instead becomes an impurity. The high performance of Example 1 proves that both free salt and APTES are indispensable.

[0060] Table 1 Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A method for preparing an iron-silicon magnetic powder core, characterized in that, Includes the following steps: S1: Activate iron-silicon powder with acid solution to obtain activated iron-silicon powder; S2: Mix the activated iron-silicon powder from step S2 with phosphoric acid solution, stir and react to obtain reaction system 1; S3: Mix reaction system 1 with ferric phosphate and / or silicon phosphate, stir until homogeneous, and obtain reaction system 2; S4: Mix γ-aminopropyltriethoxysilane with an alcohol-water mixed solvent to obtain an APTES-alcohol-water mixed system, hydrolyze it to obtain an APTES pre-hydrolyzed solution; mix the APTES pre-hydrolyzed solution with the reaction system 2 described in step S3, stir and react to obtain reaction system 3; S5: The reaction system 3 is filtered and washed and the product is collected. After molding and annealing, the iron-silicon magnetic powder core is obtained.

2. The preparation method according to claim 1, characterized in that, In step S1, the mass fraction of silicon in the iron-silicon powder is 3% to 9%.

3. The preparation method according to claim 1, characterized in that, In step S1, the acid solution includes hydrochloric acid solution and / or sulfuric acid solution, and the volume concentration of the acid solution is 1% to 5%.

4. The preparation method according to claim 1, characterized in that, In step S2, the mass fraction of the phosphoric acid solution is 1.5% to 4%.

5. The preparation method according to claim 1, characterized in that, In step S2, the stirring reaction temperature is 40~80℃, the stirring reaction time is 10~60 min, and the stirring reaction pH value is 3~5.

6. The preparation method according to claim 1, characterized in that, In step S3, the mass ratio of the iron-silicon powder to the iron phosphate is: iron-silicon powder: iron phosphate = 100: (0.5~1). And / or, the mass ratio of the iron-silicon powder to silicon phosphate is: iron-silicon powder: silicon phosphate = 100: (0.5~1).

7. The preparation method according to claim 1, characterized in that, In step S4, the mass ratio of the iron-silicon powder to γ-aminopropyltriethoxysilane is: iron-silicon powder: γ-aminopropyltriethoxysilane = 100: (0.5~5).

8. The preparation method according to claim 1, characterized in that, The stirring reaction temperature is 50~80℃, and the stirring reaction time is 30~120 min.

9. A type of iron-silicon magnetic powder core, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 9.

10. The application of the iron-silicon magnetic powder core according to claim 9 in the preparation of electromagnetic materials.

Citation Information

Patent Citations

  • Iron powder surface coating processing method

    CN103862033A